Is there an optimally diversified conglomerate? Gleaning answers from capital markets - Nejadmalayeri, Ali; Iyer, Subramanian Rama; Singh, Manohar (Review of Quantitative Finance and Accounting, 2017)
Motivated by recent productivity-based theories of diversification, we argue that only conglomerates with an optimal degree of diversification can utilize their comparative advantages across various industries and achieve economies of scope by eliminating redundancies. Evidence from both corporate bond and equity markets suggests that optimally diversified conglomerates consist of either (1) approximately five equally weighted divisions, or (2) one large core business segment that roughly accounts for 75 % sales. Moreover, the relative size of divisions has a critical impact on how diversification affects credit spreads and excess values. Nonparity among divisions correlates with greater costs that increase with the number of divisions.
Keywords: Conglomerates; Credit spreads; Equity discount; G10; G11; G12; Optimal diversification; dept.mrk

Construal-level Mindsets Enhance Behavioral Persistence in Response to Incentive Valence - Kulkarni, Atul A.; Yuan, Hong (Journal of Behavioral Decision Making, 2017)
In this research, we find that incentive valence and construal-level mindsets can interact to influence behavioral persistence on challenging tasks. An abstract mindset improves persistence in response to positively framed incentives whereas a concrete mindset improves persistence in response to negatively framed incentives. This interaction effect can be observed even when the cues inducing construal-level mindsets are not related to the incentives or the incentivized tasks. Participants in our studies were either positively or negatively incentivized to solve a set of difficult anagrams, and were primed with an abstract or a concrete mindset using spatial (Study 1) and social (Study 2) cues. The participants persisted longer in response to the positively framed incentive when primed with spatially or socially remote cues. In contrast, for the negatively framed incentive, participants persisted longer when primed with spatially or socially proximal cues. Copyright © 2017 John Wiley & Sons, Ltd.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bdm.2020
Keywords: construal-level; dept.mrk; incentive valence; mindset; persistence